PUBLIC PROVISION IN WATER AND SANITATION: AN INTER DISTRICT STUDY OF URBAN SLUMS IN JAMMU AND KASHMIR - MOHD RAFIQ KHAN; IRSHAD AHMAD RESHI; RAMEEZ RAJA (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
There seems to be an expanding slum population that has put a lot of pressure on the existing infrastructure,Drinking water and sanitation in particular.The condition is worrying because water and sanitary services have been inadequately supplied and implemented inadequatelyWith the Fluctuating condition of Jammu and Kashmir, delivering crucial facilities such as drinking water and sanitation should be a government policy priority for urban slum residents. The GOI has been incorporating certain programmes at the national as well as at the state level to Poverty alleviation, job creation and the promotion of planned urban development in public policy, yet due to the number of factors, urban slums in J&K have rapidly Increased. The objective of the paper is to test whether the provisioning of drinking water and sanitation is equitable or not across the districts. In this study we will use correlation coefficient and regression. The study uses data from various sources on the basis of secondary data. The study is also different in many aspects like data collection, time period and policy implications and gives some suggestions like Dreadful need for good governance at all government levels.